On Central European Constructs of Central Europe, or, Where Lies the Centre? - Havelka, Miloš (Dějiny – teorie – kritika, 2024)
This contribution traces the international (Schorske, Magris, Johnston etc.) and Central European (Kosík, Wandycz, Konrad, Szücs, Kiš, Kundera and others) debates on Central Europe that arose during the 1960s in particular. These were concerned not only with the Central European cultural and artistic heritage, but also with the cultural and political identity of the individual European Nations. The author offers a typology of different mental maps for Central Europe: Central Europe as Intermarium (Poland), Central Europe in the Carpathian Arch (Hungary), Central Europe between Germany and Russia (Czech Republic), nationalistic Central Europe (Slovenia) etc.